MASS MOVEMENTS' DETECTION IN HIRISE IMAGES OF THE NORTH POLE OF MARS - L. Fanara; K. Gwinner; E. Hauber; J. Oberst (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2016)
We are investigating change detection techniques to automatically detect mass movements at the steep north polar scarps of Mars, in order to improve our understanding of these dynamic processes. Here we focus on movements of blocks specifically. The precise detection of such small changes requires an accurate co-registration of the images, which is achieved by ortho-rectifying them using High Resolution Imaging Science Experiment (HiRISE) Digital Terrain Models (DTMs). Moreover, we deal with the challenge of deriving the true shape of the moved blocks. In a next step, these results are combined with findings based on HiRISE DTMs from different points in time in order to estimate the volume of mass movements.